Stimulating part-time work by legal entitlements? Evidence from a German policy experiment - Schnabel, Claus; Schank, Thorsten; Gerner, Hans-Dieter (Applied Economics Letters, 2009)
Difference-in-difference estimates indicate that the new law on part-time work in Germany has raised the share of part-time workers in those plants that already used part-time employment whereas it has not stimulated the introduction of part-time work in other plant
WiSo-Import:2015-03-25:312
Keywords: Transformation